Adaptation of Digital Technology: Case Study of Kesamben Market Traders After the Burn - Edi Murdiyanto; Imam Mukhlis (Pusat Riset dan Inovasi Nasional, 2024)
Digital technological developments require the business sector, especially small and medium businesses, to adapt. This research was carried out on Kesamben market traders in Blitar Regency after the fire disaster that occurred. The research uses a qualitative approach with case studies, which aims to explore post-fire trading conditions, especially with the development of digital technology, which is changing people's consumer behavior patterns. From the research results, most traders cannot adapt to the situation and technological developments, so they cannot survive, and some others can survive but need help maintaining turnover. There are a small number of traders who can adapt to digital technology so they can still make a profit even though they are still experiencing capital difficulties.